PERAN PENDIDIKAN AGAMA KRISTEN DAN POLA ASUH ORANGTUA DALAM MEMBENTUK PERILAKU SOSIAL REMAJA: STUDI KASUS KELUARGA KRISTEN DI TANAH MERAH, JAKARTA UTARA - Bobby Kurnia Putrawan; Pratiwi Eunike (Lembaga Penelitian STKIP Widya Yuwana, 2022)
The family is the smallest unit forming society so that the role of the family in providing a foundation or basis for them to be able to live in the midst of society is very crucial. In this case,the role of christianrelegious education and parenting has a major contribution in shaping children,s social behavior in the family. The purpose of this researchis to describe the role of Christian religious education in the family and parenting styles of parents that will shape children,s behavior in the family at adolescence. This method used is descriptive qualitative by collecting data by means of intervies and documentation. The results of the this study show that the role of Christian religious education in the clan and parenting that is carried out from an early age becomes the foundations.